Strategi Kampanye hingga Peran Partai pada Pencalonan Legislatif Petahana dan Pendatang Baru Tahun 2019 - Lombu, Rizky Julmansyah; Al Jannah, Dejehave (Universitas Indo Global Mandiri, 2023)
This research examines the campaign strategies of incumbent and newcomer legislative candidates to discover the differences or similarities in campaign strategies in the context of the 2019 elections. Through this research, the author also seeks to understand the role of political parties in nominating their members as legislative representatives. This study utilizes a qualitative descriptive method with a case study approach. Data collection techniques were conducted through interviews using the political marketing 4P approach: Product, promotion, price, and place. This research shows exciting differences in the political marketing 4P theory, specifically in Product and Promotion. Incumbent candidates with a background in civil society successfully marketed their products (ideas and work programs) to the public through door-to-door interactions and campaign materials such as educational, political books, brochures, billboards, stickers, and social media. Meanwhile, new legislative candidates should have sold their work program or vision to the public. However, they relied solely on their popularity as a celebrity background and utilized social media as a tool to campaign as legislative candidates. The party's role in nominating a cadre to become a legislative member is optional. The party serves as a platform for administrative requirements and the identity of a cadre. The party does not provide financial support to the cadre but relies on individual funds or funds from other individuals. However, the party still has responsibilities, including guidance, monitoring, and evaluation.